On the texture evolution of Mg–Zn–Ca alloy with different hot rolling paths - Q. Li; G.J. Huang; X.D. Huang; S.W. Pan; C.L. Tan; Q. Liu (Journal of Magnesium and Alloys, 2017)
In the present study, the texture evolution and mechanical anisotropy in a typical Mg–Zn–Ca alloy through hot cross rolling (CR) and unidirectional rolling (UR) were systematically studied. The results show that the rolling path greatly affects the annealed texture. The UR develops a texture with basal poles mainly distributing along the transverse direction (TD). By contrast, an ellipse-like (0002) texture with basal pole inclining largely away from the normal direction (ND) is developed after hot cross rolling and annealing. Therefore, the CR is an effective method to tailor the texture of the experimental alloy. Unfortunately, this ellipse-like texture could not reserve during the subsequent unidirectional hot rolling and annealing. Both UR and CR plates exhibit a strong planar mechanical anisotropy compared with the traditional unidirectional rolled plate. Keywords: Mg alloys, Hot cross rolling, Texture, Mechanical anisotropy